A comprehensive digital forensic investigation process model. (2016) - Montasari, Reza
A formal process model is needed to enable digital forensic practitioners in following a uniform approach and to enable courts of law in determining the reliability of digital evidence presented to them. Such a model also needs to be generic in that it can be applicable in the different fields of digital forensics including law enforcement, corporates and incident response. There does not currently exist such a comprehensive process model that is both formal and generic. To address these shortcomings, this paper proposes a model that is formal in that it can enable the digital forensic practitioners in following a uniform approach when carrying out investigations and that is generic in that it can be applied in the different environments of digital forensics.